Cover Jurnal Fitopatologi Vol. 18 No. 1, Januari 2022 (Jurnal Fitopatologi Indonesia, 2022)
This editorial contains the front cover, editorial page, and back cover of the Indonesian Journal of Phytopathology Vol. 18 No. 1, Januari 2022